Student worksheet oriented on science, technology, engineering, and mathematics (STEM) with PjBL model on acid base matter by using natural product - Imtikhana Nur Khofifah; Mitarlis Mitarlis (Jurnal Pendidikan Kimia (JPKim), 2021)
This study aims to describe the feasibility of the student worksheet developed in improving critical, creative, collaborative, and communicative thinking skills of students on acid-base material by using natural product. The student worksheet developed refers to the project-based learning model, which is integrated to science, technology, engineering, and mathematics (STEM). Method of this study uses a 4-D model (define, design, develop and disseminate), which is limited only to the development stage, and limited trials are carried out to nine students at senior high school. The feasibility of student worksheet is viewed from three aspects, namely validity, practicality, and effectiveness. The validity is viewed from the results of content and construct validity. The results obtained on each criterion show that the percentage score of 92.95% and 91.15% on very good category. The student worksheet's practicality in terms of activity observation and student response for each component obtained a percentage score of 95.18% and 88.09% on very practical category. The student worksheet's effectiveness in terms of the completeness of student learning outcomes showed an increase in the average N-Gain score of 0.84 on very high category and declared effective. Thus, the feasibility of the developed student worksheet in terms of all aspects such as percentage of scores obtained ≥ 61% in the aspects of validity, practicality and N-gain ≥ 0.3 in the aspect of effectiveness. So, the developed students worksheet oriented to STEM with PjBL model on acid base matter by using natural product is feasible for use in the learning.Keywords: acid-base, PjBL, STEM, student worksheet